Implicit asymmetric exchange rate Peg under inflation targeting regimes: The case of Turkey - Ahmet Benlialper; Hasan Cömert (Turkish Economic Association, 2013)
Especially, after the 2000s, many developing countries let exchange rates float and began implementing inflation targeting regimes based on mainly manipulation of expectations and aggregate demand. However, most developing countries implementing inflation targeting regimes experienced considerable appreciation trends in their currencies. Might have exchange rates been utilized as implicit tools even under inflation targeting regimes in developing countries? To answer this question and investigate the determinants of inflation under an inflation targeting regime, as a case study, this paper analyzes the Turkish experience with the inflation targeting regime between 2002 and 2008. There are two main findings of this paper. First, the evidence from a Vector Autoregressive (VAR) model suggests that the main determinants of inflation in Turkey during this period are supply side factors such as international commodity prices and the variation in exchange rate rather than demand side factors. Since the Turkish lira (TL) was considerably over-appreciated during this period, it is apparent that the Turkish Central Bank benefited from the appreciation of the TL in its fight against inflation during this period. Second, our findings suggest that the appreciation of the TL is related to the deliberate asymmetric policy stance of the Bank with respect to the exchange rate. Both the econometric analysis from a VAR model and descriptive statistics indicate that appreciation of the Turkish lira was tolerated during the period under investigation whereas depreciation was responded aggressively by the Bank. We call this policy stance under the inflation targeting regimes as "implicit asymmetric exchange rate peg". The Turkish experience indicates that, as opposed to rhetoric of central banks in developing countries, inflation targeting developing countries may have an asymeyric stance toward exchange rates and favour appreciation of their currencies to hit their inflation targets. In this sense, IT seems to contribute to the ignorance of dangers regarding to over-appreciation of currencies in developing countries.
Keywords: E52; E58; E31; F31; 330; Inflation Targeting; Central Banking; Developing Countries; Exchange Rates